Spin transport in the frustrated anisotropic three-dimensional XY model. (December 2016) - Lima, L.S.
Abstract: We use the SU(3) Schwinger's boson theory to study the spin transport in the frustrated anisotropic three-dimensional XY model at T =0 with single ion anisotropy. We have investigated the behavior of the spin conductivity for this model that presents exchange interactions J 1, J 2 and J ′ . We study the spin transport in the Bose–Einstein regime where we have that the t z bosons are condensed i.e. 〈 t z 〉 = 〈 t z † 〉 = t . Our results show a metallic spin transport for ω > 0 and a superconductor spin transport in the limit of DC conductivity. Abstract : Highlights: The spin current operator for the frustrated three-dimensional XY model is determined using the SU(3) Schwinger boson theory. The Matsubara's Green's functions method is employed to get the current–current correlation function. The spin conductivity is determined using the Kubo formula. The spin transport properties of the model are determined.